Influence of Carbon Dioxide and Humidity on the Stability of (La0.6Sr0.4)0.99Co1−xTixO3−δ Cathode. Issue 1 (21st January 2022) - Heinsaar, Alar; Kivi, Indrek; Möller, Priit; Kooser, Kuno; Käämbre, T.; Aruväli, Jaan; Nurk, Gunnar; Lust, Enn
Abstract : (La0.6 Sr0.4 )0.99 CoO3− δ is a very promising cathode material due to its excellent electronic and ionic conductivity. However, non-artificial air from the ambient atmosphere contains impurities such as H2 O and CO2, which cause degradation and performance loss of the cathode. Introduction of Ti into the B-site of (La0.6 Sr0.4 )0.99 CoO3− δ improves the chemical stability of the material. (La0.6 Sr0.4 )0.99 Co1−x Tix O3− δ (0 ≤ x ≥ 0.1) electrodes prepared in this work were analyzed using X-ray diffraction method (XRD), X-ray photoelectron spectroscopy (XPS), and electrochemical impedance spectroscopy (EIS). Studied (La0.6 Sr0.4 )0.99 CoO3− δ materials with Ti in B-site showed reversible degradation under gas mixture with carbon dioxide addition. Improved stability was observed for (La0.6 Sr0.4 )0.99 Co1−x Tix O3− δ materials with Ti in B-site compared to unmodified (La0.6 Sr0.4 )0.99 CoO3− δ in gas mixture containing water vapour.